2012
DOI: 10.1017/s1047951112001357
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evaluation of endothelial function in Kawasaki disease patients

Abstract: Background: Kawasaki disease is an acute systemic vasculitis. Cardiac complications are frequent and include endothelial dysfunction in patients with coronary anomalies. So far, the presence of endothelial dysfunction in patients with no coronary lesions has not been demonstrated. Peripheral arterial tonometry (Endo-PAT) measures the microvascular function in response to local ischaemia and has been validated in adult population, but its use in children is scarce. Aim: To evaluate endothelial dysfunction in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Several studies have reported that coronary microvascular circulation can be impaired in KD patients, even in the absence of coronary artery involvement (58)(59)(60). KD patients also exhibit generalized abnormalities in endothelial cell function (61)(62)(63) and myocardial flow reserve (60,63) that may persist for several years. However, the long-term risk and adverse effects of endothelial cell dysfunction after acute KD are controversial due to conflicting reports showing either the presence (61)(62)(63) or the absence (64-66) of long-term persistence of endothelial cells abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that coronary microvascular circulation can be impaired in KD patients, even in the absence of coronary artery involvement (58)(59)(60). KD patients also exhibit generalized abnormalities in endothelial cell function (61)(62)(63) and myocardial flow reserve (60,63) that may persist for several years. However, the long-term risk and adverse effects of endothelial cell dysfunction after acute KD are controversial due to conflicting reports showing either the presence (61)(62)(63) or the absence (64-66) of long-term persistence of endothelial cells abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…KD patients also exhibit generalized abnormalities in endothelial cell function (61)(62)(63) and myocardial flow reserve (60,63) that may persist for several years. However, the long-term risk and adverse effects of endothelial cell dysfunction after acute KD are controversial due to conflicting reports showing either the presence (61)(62)(63) or the absence (64-66) of long-term persistence of endothelial cells abnormalities. In line with this, a recent post hoc analysis of an international multicenter trial reported defective exercise-induced myocardial perfusion late after acute KD in 16.5%-22% of patients both with and without CAAs (67).…”
Section: Discussionmentioning
confidence: 99%
“…The oldest patient was 41 years of age and the longest time elapsed after the acute illness was 34 years . One study detected significant differences , whereas two others did not . As with all measures of endothelial function, environmental (ambient temperature, time of the day) and participant (food and alcohol intake, speaking, sleeping, position, and white coat effect) factors may affect results .…”
Section: Resultsmentioning
confidence: 98%
“…It has been demonstrated that lower Endo-PAT index is associated with increased cardiovascular risk. [37][38][39][40] The participants rested in the supine position with both hands at the same level. Specific finger probes for recording pulse amplitude volume curves were placed on the index finger of each hand, and a blood pressure cuff was placed on the non-dominant upper arm (study arm), whereas the other arm served as a the control (control arm).…”
Section: Assessment Of Endothelial Functionmentioning
confidence: 99%